Jesuit philosophy on the eve of modernity - Casalini, Cristiano 1976- (Leiden Boston Brill, 2019)
In Jesuit Philosophy on the Eve of Modernity Cristiano Casalini collects eighteen contributions by renowned specialists to track the existence and distinctiveness of Jesuit philosophy during the first century since the inception of the order.
Keywords: Iglesia católica -- Aspectos filosóficos; Jesuitas; Filosofía -- Historia -- Siglo 16o-Siglo 17o; Libros electrónicos